Behavior of RC Beams Strengthened with NSM-CFRP Strips Subjected to Fire Exposure: A Numerical Study - Al-Baghdadi, H. A.; Sabah, A. (Engineering, Technology & Applied Science Research, 2021)
The use of Near-Surface Mounted (NSM) Carbon-Fiber-Reinforced Polymer (CFRP) strips is an efficient technology for increasing flexural and shear strength or for repairing damaged Reinforced Concrete (RC) members. This strengthening method is a promising technology. However, the thin layer of concrete covering the NSM-CFRP strips is not adequate to resist heat effect when directly exposed to a fire or at a high temperature. There is clear evidence that the strength and stiffness of CFRPs severely deteriorate at high temperatures. Therefore, in terms of fire resistance, the NSM technique has a significant defect. Thus, it is very important to develop a set of efficient fire protection systems to overcome these disadvantages. This paper presents a numerical study that investigates the fire behavior of thermally insulated RC beams flexurally strengthened with NSM-CFRP strips and subjected to fire exposure according to the ISO 834 standard. The numerical study considered three-dimensional finite element models in the ABAQUS software that have been developed to simulate and predict the performance (thermal and structural response) of fire endurance tests on strengthened, uninsulated strengthened, and thermally insulated beams strengthened with NSM-CFRP strips, which were exposed to fire and had different fire insulation schemes. The insulation used was plaster from local material with a thickness range of 25 to 50mm. The variation of the thermal and mechanical properties with the temperature of the constituent materials was considered. All beams’ mechanical and thermal responses were adequately simulated using numerical models. The results of the numerical simulations were in good agreement with the experimental data. The fire behavior of the NSM-CFRP strengthened RC beams was examined and particularly the efficiency of the NSM strengthening system during the fire. The behavior in the fire of the NSM-CFRP strengthening system on the RC beams thermally protected with different fire insulation schemes was assessed. Finally, the effectiveness of fire insulation was studied.